Computer simulation model of multi-input multi-output converter using single-phase matrix converter - Mohd Shukri bin Mohd Ghazali; Rahimi Bin Baharom; Khairul Safuan Bin Muhammad; Dylan Dah-Chuan Lu (Institute of Advanced Engineering and Science, 2022)
This paper presents a multi-input, multi-output power converter system using a single-phase matrix converter (SPMC) circuit topology. In particular, this technology is of vital importance in floating production such as offshore oil and gas platforms where space is crucial, therefore requiring a reduction in equipment size and weight. The proposed circuit topology only employed a single circuit to perform energy conversion of direct current (DC) to alternating current (AC), DC to DC, AC to DC, and AC to AC operations, thus can reduce the power losses resulting in high power density. As a result, it can promise technological advancement and convergence, hence, support the manufacturing sector transition to industry 4.0, and in line with the United Nation’s sustainable development goals. The proposed converter model will be validated in terms of electrical circuit operations through the computer simulation (MATLAB/Simulink) software.